Assessment of clinical and esthetic parameters in isolated gingival recession treated with coronally advanced flap versus bidirectionally positioned flap: A 6-month follow-up study - Chakradhar Sana; Ashita Uppoor; Sangeeta Umesh Nayak; Neetha Shetty; Priyanka Paramita Sahu; Pragya Atray (Journal of Indian Society of Periodontology, 2025)
Background: In periodontal therapy, marginal gingival recession (GR) is a recurrent finding that emphasizes the importance of using efficient root coverage approaches. The bidirectionally positioned flap (BPF) offers a unique strategy that merits investigation. This study aims to evaluate the clinical outcomes of BPF and conventional coronally advanced flap (CAF) for treating isolated GRs classified as Class I by Miller. Materials and Methods: Sixteen participants were included in the study (8 in each group). Clinical parameters, including the plaque index, gingival thickness (GT), recession height (RH), probing pocket depth, clinical attachment level (CAL), keratinized tissue height (KTH), RH, and Visual Analog Scale (VAS), were recorded during the study. At 6 months, both treatment modalities resulted in significant root coverage (P < 0.01), with an average coverage of 2.5 mm for the BPF group and 2.38 mm for the CAF group. Results: Both treatments showed comparable outcomes, with no significant differences in relative height loss. Additionally, GT, KTH, probing depth, and CAL remained consistent across both groups, highlighting their similar effectiveness. Conclusion: This study’s conclusions highlight the effectiveness of BPF and CAF in improving root coverage over 6 months, with BPF showing promise as a therapeutic intervention for isolated GR.